Organisational culture in sport - a systematic review - Maitland, A.; Hills, L. A.; Rhind, D. J. (Sport Management Review, 2015)
The purpose of this paper was to systematically review the study of organisational culture in sport. The choice of research paradigms, methods, interests, perspectives, and definitions and operationalisation of organisational culture used in 33 studies was examined. This highlighted the variety of ways that culture has been studied in sport and the range of interests explored in the research, including informing athlete development, the link between the strength of culture and organisational performance and understanding the forces driving organisational diversity. Unlike the wider organisational culture literature, there has been a preference in sport to assume that culture was a variable to manipulate in an organisation. The opportunity to widen approaches to study organisational culture in sport is discussed, such as broadening the methods used to conduct studies, including both coaches and athletes in the population studied and using the fragmentation perspective, where ambiguity and conflict are considered in understanding culture.